Spectrophotometric Evaluation of Enamel Color Variation Using Infiltration Resin Treatment of White Spot Lesions at One Year Follow-Up - Roberto Lo Giudice; Frank Lipari; Francesco Puleio; Angela Alibrandi; Fabrizio Lo Giudice; Cristina Tamà; Evgenia Sazonova; Giuseppe Lo Giudice (Dentistry Journal, 2020)
The aim of this study is to evaluate the color changes and the stability at a 1-year follow-up of white spot lesions (WSLs) treated with an infiltrating technique by using etching and TEGDMA resin. The color of 22 white spot lesions and the sound adjacent enamel (SAE) were assessed with a spectrophotometer at T0 (baseline), T1 (after treatment), and T2 (1 year after). The color change ΔE (WSLs-SAE) at T0 vs. T1 were compared to evaluate the camouflage effect efficiency, and at T1 vs. T2 to assess the stability of outcomes. To evaluate the effect on the treatment outcome of gender, the presence or not of previous orthodontic treatment, WSLs onset more/less than 10 years, the age of the patient, and the ΔE WSL (T0 vs. T1) was analyzed. The difference between ΔE (WSLs-SAE) at T0 and T1 resulted in statistical significance (p < 0.01). No statistical difference was found between ΔE (WSLs-SAE) at T1 vs. T2. The variables considered showed no statistical differences in treatment outcomes. The results of our investigation show that the technique used is immediately effective and the camouflage effect keeps up and steady one year after treatment. Such results do not appear to be influenced by analyzed clinical variables.